'Be creative' in Bangladesh? Mobility, empowerment and precarity in ethical fashion enterprise. Issue 6 (2nd November 2019) - Khan, Rimi
ABSTRACT: The rise of creative, ethical entrepreneurship within the global garment industry promises new kinds of empowerment and mobility for Asian workers. 'Ethical fashion' brings alternative ways of valuing cultural commodities by imagining South Asian textile workers as potentially creative, entrepreneurial, and empowered. However, ethical fashion enterprise also brings particular forms of instability and risk. Through an analysis of two ethical fashion brands in Bangladesh – Aarong and Bhalo – this article demonstrates the disconnect between an idealized discourse of empowerment, and the material conditions of precarity and immobility that characterize fashion enterprise, especially in its 'ethical' forms. The apparent mobility of notions of ethics and empowerment championed by ethical fashion brands are shadowed by the 'predatory mobility' of global capital. While transnational flows of capital, creativity and ethics can bring about productive connections and exchange between designers, workers, and consumers in and around Asia, these take place in a context of ongoing economic insecurity.